EVALUASI LETAK OBJEK-OBJEK WISATA PADA KOTA SINGKAWANG DENGAN METODE SPACE SYNTAX - Muhammad Alif Khairil Akbar; Bontor Jumaylinda Br Gultom; Affrilyno Affrilyno (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Tourism is an important activity in urban development because it is able to increase economic factors that affect income increases, increase business and employment levels and reduce poverty, as well as one of the leading sectors that become income for the government. The success of tourism is easy to observe if there is an increase in the number of tourists who come from year to year. Location is a factor that greatly affects the increase in the number of tourists because a good location can increase the value of decisions in visiting tourist objects. This shows that the better the location, the higher the value of tourists' decisions in visiting tourist objects. Attractions have 4 development aspects in it which are called 4A aspects consisting of attractions, amenities, accessibility, and additional services. These aspects become benchmarks in seeing the offer of the location of a tourist attraction. The research was conducted with the aim of determining the location of the tourist attraction in Singkawang City based on the 4A aspect of the tourist attraction. This study uses a quantitative approach that uses spatial syntactic analysis to assess accessibility, and scores to generate findings. From the analysis, the results show that the tourist attraction in Singkawang City has sufficient value within the limits of possibilities and facilities that can be accessed at the tourist attraction.